Communication through in‐person interpreters: a qualitative study of home care providers' and social workers' views. Issue 1 (21st November 2012) - Brämberg, Elisabeth B; Sandman, Lars
<x xml:space="preserve">Abstract</x> Aims and objectives To describe the experiences of home care providers and social workers in communication, via in‐person interpreters, with patients who do not share a common language, and to offer suggestions for practice based on this description. Background The use of interpreters is essential for successful communication to provide equal access to health care for patients not sharing a common language with care providers. Successful bilingual communication is probably even more complex within the home care services with its focus on medical treatment, care and daily support in relation to the more exclusive focus on medical treatment within hospital care. Design An explorative, qualitative, descriptive study. Methods Data were collected in seven focus group interviews. A total of 27 persons, working as registered nurses, assistant nurses and social workers in municipal home care, participated. The analysis was inspired by inductive content analysis. Results The results express a traditional view on interpretation where the in‐person interpreter is supposed to act to a greater or lesser extent as an objective and neutral conduit or communicator of what is said. The interpreter is also expected to observe when medical terms and other concepts need to be explained, which thus exceeds the basic role as a communicator of what was said. Conclusions This study emphasises the need to view the interpreter as an active and explicit party in a three‐way communication. Relevance to clinical practice Viewing the interpreter as an active and explicit party in a three‐way communication and as an essential part of the care team might reduce the possible threat to patient confidentiality, and could contribute to solve the problem of interpreting the patient's non‐verbal signs.